Interspecific variation in large mammal responses to human observers along a conservation gradient with variable hunting pressure. (30th April 2014) - Kiffner, C.; Kioko, J.; Kissui, B.; Painter, C.; Serota, M.; White, C.; Yager, P.
Abstract When subject to anthropogenic hunting risks, wildlife populations may adjust their anti‐predator behaviour; however, such plastic response has rarely been assessed. We assessed the response of eight species (African elephant, Maasai giraffe, plains zebra, common wildebeest, Grant's gazelle, impala, Thomson's gazelle and Kirk's dik dik) towards human observers in a landscape with variable anthropogenic hunting pressure. Using logistic regressions, we tested the effect of habitat type, group size, distance to observer and conservation status of the area on the likelihood of animal behavioural adjustments (walking away, fleeing or giving alarm calls). Habitat type did not affect the likelihood of a response towards humans. Dik diks were less likely to respond towards human when they were in larger groups. In contrast, zebras and Thomson's gazelles were marginally significantly more likely to show a response when in larger groups. Responses of all species were significantly or marginally significantly (elephant) lower with increasing distance from observers (an increase by one meter distance changed the response likelihood by 0.01–0.30). Four species (zebra, wildebeest, impala, dik dik) showed a gradual adjustment of responsiveness according to conservation status and were most responsive in non‐protected and least responsive in fully protected areas (0.02–0.29 times less responsive in fully vs. multiple‐use areas). However, elephants, giraffes and both gazelle species did not significantly adjust their behaviour according to conservation status. This suggests that the behaviour of some species can be used as useful indicator of conservation status of an area whereas the behaviour of other species does not allow discriminating between management types. More generally, our study highlights the importance of assessing and controlling illegal hunting in multiple‐use areas and suggests a stronger consideration of human‐induced risk effects in the conservation of ungulates.